1981
DOI: 10.1007/bf02125525
|View full text |Cite
|
Sign up to set email alerts
|

The amantadine-sensitivity of recombinant and parental influenza virus strains

Abstract: Several wild-type influenza A strains together with recombinants derived from these strains, were tested for sensitivity to amantadine using the in vitro techniques of inhibition in egg-bit culture and plaque reduction in MDCK cells. The results obtained were analysed with reference to the derivation of the recombinants. Susceptibility to amantadine was related to the gene coding for matrix protein, and these data are in agreement with previous reports of studies using other series of influenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Second, we determined the acid dissociation pK, of Hln both with and without 6-Cy in solution utilizing different wavelengths. At 530 nm we found pK, 3.404 f 0.005 in the presence of 6-Cy and 3.404 & 0.008 in the absence. At 509 nm we observed pKa 3.408 f 0.012 in the absence of 6-Cy.…”
mentioning
confidence: 65%
“…Second, we determined the acid dissociation pK, of Hln both with and without 6-Cy in solution utilizing different wavelengths. At 530 nm we found pK, 3.404 f 0.005 in the presence of 6-Cy and 3.404 & 0.008 in the absence. At 509 nm we observed pKa 3.408 f 0.012 in the absence of 6-Cy.…”
mentioning
confidence: 65%
“…Dose response curves with the A/PR/8/34 virus growing on RAW 264.7 cells revealed several orders of magnitude more inhibition by berberine than with amantadine, a well characterized M2 inhibitor. The A/PR/8/34 virus is known to be relatively resistant to amantadine [50] and its susceptibility to berberine may indicate that berberine is working through a distinct mechanism. In addition, we showed that berberine can inhibit the influenza A-induced production of TNF-α and PGE 2 from RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 98%